Rapid identification of radical scavenging compounds in blueberry extract by HPLC coupled to an on-line ABTS based assay and HPLC-ESI/MS - Kim, Chul Young; Lee, Hee Ju; Lee, Eun Ha; Jung, Sang Hoon; Lee, Dong-Un; Kang, Suk Woo; Hong, Sae An; Um, Byung-Hun (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2008)
This study employed high performance liquid chromatography (HPLC) coupled to an on-line ABTS(+) radical scavenging detection (RSD) system along with HPLC-clectro spin impact/mass spectrometry (ESI/MS), to rapidly determine and identify antioxidant Compounds Occurring in blueberry extract. The extract was separated by HPLC, and then the radical scavenging activities of the separated compounds were evaluated by the on-line coupled ABTS(+)-RSD system. The negative peaks of the ABTS(+)-RSD system, which indicates the presence of antioxidant activity, were monitored by measuring the decrease in absorbance at 734 nm. The active components in the blueberry extract were identified by HPLC-ESI/MS using their MS spectra and retention times. According to the data acquired from the on-line HPLC-ABTS'-based assay and HPLC-ESI/MS systems, the antioxidant compounds detected in the blueberry extract were identified as chlorogenic acid and 11 anthocyanins.
Keywords: ANTIOXIDANT ACTIVITY; PHENOLIC-COMPOUNDS; IN-VITRO; L.; ANTHOCYANINS; CYANIDIN; CONSTITUENTS; GROWTH; FRUITS; WINES